Pemaknaan Mengapa Luka Tidak Memaafkan Pisau Karya M. Aan Mansyur Melalui Semiotik Riffaterre - Andalas, Maharani Intan; Dinasti, Aqilla Elza (UM Purwokerto Press, 2024)
Indonesian poetry has undergone significant development to date with the publication of various poetry anthologies and recognition of poets' achievements in their works through literary awards. Nevertheless, a study of the award-winning poetry is still required to reveal its meaning. The significance of poetry is inseparable from the sign system. Mengapa Luka Tidak Memaafkan Pisau by M. Aan Masyur is a poetry anthology that won two literary awards in 2021. The poet's expressions, ideas, and feelings are manifested through the signs in the anthology. This research aims to reveal the significance of Mengapa Luka Tidak Memaafkan Pisau by M. Aan Masyur by using Riffaterre's semiotic theory. The research method is qualitative, with steps in data determination, data collection, data analysis, and drawing conclusions. From the research results, the significance of awareness of life, deep love, and the human inability to explain everything that shows God's greatness is obtained in this anthology's poems.